Selection of environmentally safe open-pit technology for mining water-bearing deposits - Sobko, B.; Drebenstedt, C.; Lozhnikov, O. (Розробка родовищ, 2017)
Purpose. Substantiation of environmentally acceptable technologies for surface mining of water-bearing placer deposits, taking into account the parameters of mining systems elements and areas damaged during mining of mineral deposits. Findings. To conduct the research, we proposed to use index Δ which compares the actual position of inter-ramp angles and the inside dump angles with the maximum permitted values. The dependences of concentration degree KK and area of workings Str on index Δ allow to infer that the technological scheme with a rotary excavator is more environmentally sound than the scheme with hydraulic excavators. Application of the former technological scheme makes it possible to reduce the area of disturbed lands by 8%. In the proposed scheme of mining Motronivske placer deposit, the concentration degree KK reaches the maximum value 0.7, which corresponds to the minimum area of workings.